Maltrato infantil familiar y aprendizaje significativo en niños del primer grado de primaria de I.E.P.S.C. N° 601582 Agustín Rivas Vásquez, distrito de Fernando Lores Tamshiyacu 2022 - Izquierdo Ferreyra, Jhaneska Viviana (2024)
The general objective of the study is to explain the relationship that exists between family child abuse and significant learning in children in the first grade of Primary I.E.I.P.S.C. N° 601582 Agustín Rivas Vásquez, Fernando Lores District[1]Tamshiyacu 2022; The applied type of research was used, as a cross-sectional correlational design; population of 297 and a sample of 50 students from the I.E.I.P.S.C. Agustín Rivas Vásquez, the instruments were two questionnaire surveys to collect the data, the study presents as a result, after having verified with Kendall's Tau-b coefficient where its calculated value was 0.217 and its approximate significance of 0.035 (p < 0.05), interpreting that as the level of significant learning increases, the level of child abuse decreases; At a significance level of 5%, it is concluded that there is a statistically significant relationship between family child abuse and significant learning in children in the first grade of primary school, Agustín Rivas Vásquez Educational Institution. The general hypothesis posed in the investigation.